2020
DOI: 10.1136/bmjgh-2020-003934
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety and acceptability of medical abortion at home versus in the clinic: a systematic review and meta-analysis in response to COVID-19

Abstract: BackgroundIncreased access to home-based medical abortion may offer women a convenient, safe and effective abortion method, reduce burdens on healthcare systems and support social distancing during the COVID-19 pandemic. Home-based medical abortion is defined as any abortion where mifepristone, misoprostol or both medications are taken at home.MethodsA systematic review and meta-analysis of randomised controlled trials (RCTs) and non-randomised studies (NRSs) were conducted. We searched databases from inceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 44 publications
3
43
0
2
Order By: Relevance
“…An analysis of more than 52 000 MA in the UK showed that the telemedicine‐hybrid model for care adopted in response to the pandemic was as effective, safe, acceptable and more accessible than conventional care provided in the first 3 months of 2020 ( 16 ). These findings align with other research showing that home-based and telemedicine first trimester MA are safe with high rates of efficacy and acceptability ( 17 , 18 ). Existing research in several high-income nations also suggests providers may be interested in maintaining the liberalized practice changes implemented since the beginning of the COVID-19 pandemic ( 19 , 20 ).…”
Section: Introductionsupporting
confidence: 91%
“…An analysis of more than 52 000 MA in the UK showed that the telemedicine‐hybrid model for care adopted in response to the pandemic was as effective, safe, acceptable and more accessible than conventional care provided in the first 3 months of 2020 ( 16 ). These findings align with other research showing that home-based and telemedicine first trimester MA are safe with high rates of efficacy and acceptability ( 17 , 18 ). Existing research in several high-income nations also suggests providers may be interested in maintaining the liberalized practice changes implemented since the beginning of the COVID-19 pandemic ( 19 , 20 ).…”
Section: Introductionsupporting
confidence: 91%
“…3 Several models for using telemedicine to facilitate medical abortion have been described but most existing trials are small, and many required attendances to have medicines administered, an ultrasound scan or blood tests. 7 , 38 Our study is the first to assess a real‐world no‐test telemedicine abortion care pathway in a national population. This new national model demonstrates how a permissive framework for medical abortion can deliver significant quality improvements to those needing to access abortion care.…”
Section: Discussionmentioning
confidence: 99%
“…Some posters described self-managed techniques versus clinical venues for abortion care. While receiving and using medication abortion by mail can be safe, effective, and affordable [33,34], it is not legally sanctioned in the U.S. While some people seeking abortion may prefer mail-based services to abortion clinics even if they can access and afford both, Reddit posts documented that the costs and logistics of in-clinic abortions may back people into illegal services such as Aid Access.…”
Section: Discussionmentioning
confidence: 99%